Maaperän pH ja sen vaikutus arktis-alpiiniseen kasvillisuuteen - Puhjo, Elina (Helsingfors universitet, 2016)
There is a lack of studies focusing on the fine scale variation of soil pH. Soil pH has an important role for plants as it affects nutrient availability through microbe decomposition activity. Arctic-alpine vegetation is adapted to a specific pH-environment and there are differences in the distribution of plant functional types along a pH-gradient. The aim of this research is to clarify how soil pH varies in fine scale and how strongly it affects species community composition and species richness. The study site includes 21 grids in a topographically changing environment on the Saana-massif. Soil samples were collected from 378 plots. Soil pH values were interpolated to neighboring plots later. Vascular plants were identified and soil moisture and temperature were measured in the same 378 plots as pH. Measuring took place during summers 2011±2013. For each plot, elevation from sea level was measured and the potential annual solar radiation was estimated using slope aspect and gradient. The correlation between environmental variables and vascular plant community composition was tested using NMDS-ordination method. Species richness for evergreen shrubs, deciduous shrubs, forbs and graminoids was modelled using GAM and GBM models. The explanatory power of pH was studied by comparing the pH-model to the base model. Soil pH varies dramatically across the fine scale environment. Most of the non-acidic sites are located in south-west slopes of Saana-massif. Soil pH and moisture were the key drivers of plant community composition. Forbs were located in the non-acidic part of the pH gradient, while other functional types were scattered. Soil pH and moisture were the most important variables affecting species richness, especially with forbs and graminoids. In the case of shrubs, soil pH was less important. Including soil pH into the models improved the predictions of species richness in every functional types. Species richness correlated positively with soil pH and moisture for every functional type. The fine scale ...